Untersuchung der Hochvoltstabilität und Tiefentladung von dotierten LiNi0,5Mn1,5O4-Hochvoltspinellen - Höweling, Andres (Schriftenreihe des Instituts für Angewandte Materialien, Karlsruher Institut für Technologie, 2018)
Due to its high operating voltage the so-called high voltage spinel (LiNi0,5Mn1,5O4) is a promising cathode material. In this work the kinetics of the capacity loss during cycling and its change due to different coatings are analyzed. In a second part the electrochemical behavior for the insertion of a second lithium per formula unit is discussed for different doped spinel materials.